Escape from the prison of love: caloric identities and writing subjects in fifteenth-century Spain - Folger, Robert (North Carolina studies in the Romance languages and literatures, 2009)
"Escape from the Prison of Love is an exploration of medieval modes of subject constitution and their transformation in fifteenth-century Spanish sentimental romance, with a particular focus on Diego de San Pedro's Carcel de amor. Drawing on premodern psychological models, Robert Folger argues that courtly self-fashioning through amatory performance provided an alternative and threat to the medieval gradual build-up of the self through hexis and habitus. In the light of the unsettling gender implications for the courtly lover, says Folger, the authors of sentimental fiction explored new ways of subject constitution based not on passionate attachment but on identification. Carcel de amor shows how new forms of writing and reading techniques and authorship provided an avenue for a new notion of interiority that was essential to the Golden Age of Spanish literature."--Provided by publisher